PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN FLASHCARD TERHADAP KEMAMPUAN MEMBACA SISWA KELAS 1 SDN SIWALANKERTO II SURABAYA - Putri Damayanti, Al Febri; Umar Susanto, Rudi; Kasiyun, Suharmono; Ghufron, Syamsul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine students' reading ability before and after using flashcard learning media and to analyze the effect of using the media on the reading ability of first-grade students at SDN Siwalankerto II Surabaya. This study is motivated by the low initial reading ability of students caused by the use of learning media that is less interesting and tends to be monotonous. This study uses a quantitative approach with a pre-experimental design and a one group pretest-posttest design. The research sample consisted of 21 first-grade B students selected using a purposive sampling technique. Data collection techniques were carried out through reading tests in the form of pretests and posttests, while data analysis used descriptive statistics and paired sample t-tests. The results of the study showed that students' reading ability before using flashcard media was in the sufficient category with an average score of 67.38 and most students had not reached the Minimum Completion Criteria (KKM). After being given treatment using flashcard media, students' reading ability experienced a significant increase, marked by an increase in the average score and the number of students who achieved learning completion. The results of the hypothesis test indicate a significant effect of flashcard use on students' reading ability.